Stress is associated with an increased risk of recurrent seizures in adults. (18th April 2017) - Baldin, Elisa; Hauser, W. Allen; Pack, Alison; Hesdorffer, Dale C.
Summary: Objective: The literature is sparse on the complex interrelationships between stressors, depression, anxiety disorders, and epilepsy. We hypothesized that a relationship exists between stress and epilepsy. We evaluated whether markers of stress are associated with seizure recurrence in a low income community‐based cohort of adults with single unprovoked seizure or newly diagnosed epilepsy. Methods: We ascertained adult residents of Northern Manhattan and Harlem, New York City, with a first unprovoked seizure or newly diagnosed epilepsy, between December 2010 and January 2013. At enrollment, we collected information about seizure phenomenology, demographics, clinical information, and measures of stress (environmental stress, stressful life events, facets of allostatic load—i.e., the cumulative effect of adaptation to stress, psychiatric disorders, and low collective efficacy). Collective efficacy assesses neighborhood characteristics and incorporates social cohesion and informal social control. All subjects were followed for 2 years for further seizures. Cox proportional hazard regression models were used to estimate the hazard ratios of seizure recurrence during the 2 years of follow‐up. Results: We identified 52 subjects (64.2%) with a single unprovoked seizure and 29 (35.9%) with newly diagnosed epilepsy. Seizure recurrence was recorded in 38.5% (N = 20) of subjects with a single unprovoked seizure and in 69% of those with epilepsy (N = 20) (p = 0.01). In the overall sample, the hazard of seizure recurrence was increased by lifetime generalized anxiety disorder (3.0‐fold) and by low collective efficacy (2.7‐fold). In a second model, the hazard was increased by lifetime mood disorder (2.1‐fold) and low collective efficacy (2.5‐fold). Significance: Markers of stress (i.e., low collective efficacy, lifetime mood disorder, and lifetime generalized anxiety disorder) were associated with an increased risk for seizure recurrence in adults with a single unprovoked seizure or newly diagnosed epilepsy. Stress‐reducing interventions, such as mindfulness, may be a useful, safe, and inexpensive adjunctive treatment for epilepsy.